Ответы 1

  • 5^(x+1) - 5^(x - 1) = 24;5^x * 5^1 - 5^x * 5^(-1) = 24;5^x * 5 - 5^x * (1/5) = 24;5^x * (5 - 1/5) = 24;5^x * (5*5 - 1)/5 = 24;5^x * (25 - 1)/5 = 24;5^x * 24 = 24 * 5;5^x = 5^1;Следовательно, x = 1.Проверка: 5^(x+1) - 5^(x - 1) =5^(1+1) - 5^(1 - 1) =5^2 - 5^0 = 25 - 1 = 24.Ответ: x = 1.
    • Автор:

      skyese5z
    • 4 года назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years